Assessing conflict between early neornithischian tree topologies. (2nd September 2021) - Brown, Emily E.; Butler, Richard J.; Barrett, Paul M.; Maidment, Susannah C. R.
Abstract : The phylogenetic relationships of the species commonly referred to as 'hypsilophodontids' remain one of the key questions in ornithischian dinosaur research, having profound implications for understanding the origin, evolution and taxonomical compositions of several more recently evolved neornithischian clades. Recent phylogenetic analyses have recovered two conflicting placements for these taxa: (1) primarily within Cerapoda (Ornithopoda + Marginocephalia), as a paraphyletic assemblage of early ornithopods; and (2) primarily outside of Cerapoda, within the clade Thescelosauridae. Here we assess three recent independent neornithischian phylogenetic studies that have recovered topologies congruent with one of these placements. We compare the compositions of these data matrices and test how each of them responds to manipulation of taxa and characters. The positions in which controversial clades are recovered is shown to be highly dependent on the sample of taxa analysed; however, taxon incompleteness or instability is not a contributing factor in altering topology. Character completeness and homoplasy is shown not to significantly alter tree topology either, although these factors can affect resolution. In one matrix investigated, femoral and dental characters are found to provide disproportionate support for the placement of key taxa outside of Cerapoda, and the exclusion of a small number of these characters results in 'hypsilophodontids' falling within Ornithopoda. In contrast, matrices that originally recovered 'hypsilophodontids' within Cerapoda are comparably more stable, with this array of taxa remaining in a consistent position throughout all analyses. There is still much work to be done to resolve these relationships, but our study provides several suggestions for future analyses with the aim of resolving areas of conflict within the neornithischian tree.